2021
DOI: 10.1080/21655979.2021.2014386
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown long non-coding RNA HCP5 enhances the radiosensitivity of esophageal carcinoma by modulating AKT signaling activation

Abstract: Recently, long noncoding RNAs (lncRNAs) have been revealed to participate in cancer therapy. Especial in tumor radiotherapy, lncRNAs usually could enhance or restrict the radiosensitivity in different ways. LncRNA HCP5 is highly expressed in esophageal cancer and influenced the malignant behaviors of esophageal cancer cells. However, this study dedicates to clarify if lncRNA HCP5 affects the radiosensitivity of esophageal carcinoma. The expression levels of HCP5 in esophageal cancer and adjacent noncancerous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…DNM3OS can also promote tumor progression in gastric cancer [34] and oral cancer [35]. HCP5 has been studied in several kinds of tumors, including ovarian [36], esophageal [37], gastric [38], and colorectal cancer [39]. It has been demonstrated that HCP5 can target miR-525-5p/ PRC1 signaling pathway and can target the Wnt/betacatenin pathway [36].…”
Section: Discussionmentioning
confidence: 99%
“…DNM3OS can also promote tumor progression in gastric cancer [34] and oral cancer [35]. HCP5 has been studied in several kinds of tumors, including ovarian [36], esophageal [37], gastric [38], and colorectal cancer [39]. It has been demonstrated that HCP5 can target miR-525-5p/ PRC1 signaling pathway and can target the Wnt/betacatenin pathway [36].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing research has found that the radiotherapy resistance mediated by ncRNAs is associated with the AKT pathway. For instance, increased expression of lncRNA HCP5 has been identified by Guo et al to induce radiotherapy resistance in esophageal cancer tissues by promoting AKT activation through regulating miR-216a-3p/PDK1 axis [ 164 ]. Another well-documented lncRNA DUXAP8 increases radiotherapy resistance in breast cancer cells by activating the PI3K/AKT/mTOR signaling pathway [ 165 ].…”
Section: Ncrnas Effect Cancer Therapeutic Tolerance Through Metabolic...mentioning
confidence: 99%
“…A study revealed that lncRNA HCP5/miR-216a-3p/PDK1 enhanced radiotherapy resistance in KYSE30 and TE-1 cells by activating the AKT signaling pathway ( 114 ). Similarly, LINC00963/miR-10a/spindle and kinetochore associated complex subunit 1 was found to increase cisplatin resistance in TE-1 and TE-1/DDP cells, thereby promoting CDX growth ( 115 ).…”
Section: Lncrnas Upregulated In Esccmentioning
confidence: 99%